Depression diagnosis by deep learning using EEG signals: A systematic review - Safayari, Atefeh; Bolhasani, Hamidreza (Medicine in novel technology and devices, 2021)
Depression is considered by WHO as the main contributor to global disability and it poses dangerous threats to approximately all aspects of human life, in particular public and private health. This mental disorder is usually characterized by considerable changes in feelings, routines, or thoughts. With respect to the fact that early diagnosis of this illness would be of the critical importance in effective treatment, some developments have occurred in the purpose of depression detection. EEG signals reflect the working status of the human brain which are considered the most proper tools for a depression diagnosis. Deep learning algorithms have the capacity of pattern discovery and extracting features from the raw data which is fed into them. Owing to this significant characteristic of deep learning, recently, these methods have intensely utilized in the diverse research fields, specifically medicine and healthcare. Thereby, in this article, we aimed to review all papers concentrated on using deep learning to detect or predict depressive subjects with the help of EEG signals as input data. Regarding the adopted search method, we have finally evaluated 22 articles between 2016 and 2021. This article which is organized according to the systematic literature review (SLR) method, provides complete summaries of all exploited studies and compares the noticeable aspects of them. Moreover, some statistical analyses have been performed to gain a depth perception of the general ideas of the latest pieces of research in this area. A pattern of a five-step procedure has also been established by which almost all reviewed articles have fulfilled the goal of depression detection. Finally, open issues and challenges in this way of depression diagnosis or prediction and suggested works as the future directions have been discussed. •Providing comprehensive summaries of all latest articles related to depression diagnosis by deep learning using EEG signals.•Making comparisons between major aspects and concepts of reviewed articles.•Analyzing all inspected papers in the point of a introduced five-stage pattern.•Discussing main issues which are correlated with our topic.